2022
DOI: 10.1177/20552076221074127
|View full text |Cite
|
Sign up to set email alerts
|

Smart health via mHealth? Potentials of mobile health apps for improving prevention and adherence of breast cancer patients

Abstract: Objective Today there are several health and medical apps (mHealth) in app stores. Germany is the world's first country that introduced apps paid by the regular health insurance service. Even though breast cancer is the most common cancer in women, mHealth for breast cancer has been largely unexplored. Methods A total of 33 apps from two major mobile application marketplaces (Google Play Store/Android; App Store/iOS) have been selected for analysis. Results The app analysis shows that there are currently only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…However, there are little restrictions on who can develop and publish an app and regulatory organizations rarely check the validity of the health information provided in these apps. 25 , 26 This has resulted in many websites 27 , 28 and mHealth apps providing unclear quality of information for patients, 3 , 28 33 which is particularly troublesome as patients who are not familiar with medicine topics often cannot differentiate between trustworthy, reliable and less relevant information, putting users’ health and safety at risk. 27 , 28 , 33 While mHealth apps have a great potential to aid women in adopting healthier lifestyles, raising awareness about the significance of breast cancer prevention and offering dependable and accurate information, prior reviews about breast cancer apps are still subjected to various limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are little restrictions on who can develop and publish an app and regulatory organizations rarely check the validity of the health information provided in these apps. 25 , 26 This has resulted in many websites 27 , 28 and mHealth apps providing unclear quality of information for patients, 3 , 28 33 which is particularly troublesome as patients who are not familiar with medicine topics often cannot differentiate between trustworthy, reliable and less relevant information, putting users’ health and safety at risk. 27 , 28 , 33 While mHealth apps have a great potential to aid women in adopting healthier lifestyles, raising awareness about the significance of breast cancer prevention and offering dependable and accurate information, prior reviews about breast cancer apps are still subjected to various limitations.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 , 33 While mHealth apps have a great potential to aid women in adopting healthier lifestyles, raising awareness about the significance of breast cancer prevention and offering dependable and accurate information, prior reviews about breast cancer apps are still subjected to various limitations. Some have only focused on breast cancer patients or survivors, 30 , 34 , 35 while others conducted app store searches from other continents than Europe, 35 , 36 or only analysed app content and not their quality. 30 , 32 , 34 36 Consequently, we set out to provide a review of mobile apps available on the German Google Play or Apple App store covering particularly apps focusing on breast cancer prevention and education.…”
Section: Introductionmentioning
confidence: 99%
“…In oncology, applications are included in current recommended therapies (8). Nevertheless, health prevention is essential, and the studies exploring the DHT, particularly telephone reminders or messages, for cancer screening participation found that they do have effect (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…H-F genre on iOS App Store refers to the "Apps related to healthy living, including stress management, fitness, and recreational activities." 1 H-F mobile apps allow users to access and keep track of their H-F data continuously, 18 , 19 which helps in changing health behavior, 20 , 21 such as monitoring weight and diet, 22 managing a disease 23 or promoting medication adherence. 24 As discussed earlier, the pandemic has impacted access to H-F facilities and increased the use and development of new mobile apps.…”
Section: Introductionmentioning
confidence: 99%